THE INFLUENCE OF INFLUENCER MARKETING, BRAND AWARENESS, AND VIRAL MARKETING ON PURCHASE DECISIONS OF SCARLETT PRODUCTS (A SURVEY OF THE COMMUNITY IN KUNINGAN REGENCY): A Survey of the Community in Kuningan Regency - Oktaviani, Winda; Gunawan, Wely Hadi (Gapenas Publisher, 2025)
Major changes in society were the result of technological advancements that had influenced all aspects of civilization and culture. Various types of information could be easily accessed. Many companies had utilized social media to market or promote their products, allowing them to attract a large number of consumers in making purchasing decisions—one example being the decision to purchase Scarlett beauty products. The purpose of this study was to determine the influence of influencer marketing, brand awareness, and viral marketing on purchase decisions (a survey of Scarlett users in Kuningan Regency). This research was a descriptive quantitative study. The population in this study consisted of the community in Kuningan Regency. The sample comprised 100 individuals. The sampling technique used in this study was non-probability sampling. Data were collected using a questionnaire with a value range of 1 to 10. Data analysis was carried out using multiple linear regression analysis with the assistance of SPSS 25 software. The results of this study showed that: (1) Influencer Marketing, Brand Awareness, and Viral Marketing simultaneously influenced purchase decisions; (2) Influencer Marketing influenced Purchase Decisions; (3) Brand Awareness influenced Purchase Decisions; and (4) Viral Marketing influenced Purchase Decisions.